A Framework to Improve the Net Promoter Score Through Focused Communication at Specific Touch Points of a Private Hospital in India - Varghese, Shiny (Digital Repository of Theses, 2025)
A happy customer serves as the brand's representative, might accept, and support a service. Every business still operates on the same fundamentals: the client brings the business. The firm takes note of what customers have to say and improve as per the requirement continues to exist and thrive their business. When they are pleased, they will tell a few people about the experience and the business; when they are dissatisfied, it will multiply and reach a far larger audience. In healthcare facilities too this is not different. Having satisfied customers is the measurement of adherence to the expectation, and the fulfillment of the expectation. Many times, it is noted that the communication gap is the major reason for the customer not being satisfied with the services. The experience the patient receives at every touch point matters for the overall satisfaction during the encounter or stay. If there are challenges foretold, it would help them modify their perception, as they know what to expect. So, communication at every touch point makes a huge difference to the patient to make the event a memorable one. It was noticed in a private hospital in India, that a few touchpoints get good satisfaction scores whereas a few touch points get many negative scores, which was below the targeted score of the organization. When the scores were averaged, the total satisfaction score was not as desired, although a few touchpoints were getting exceptionally good scores. It was also noted that whether the good or bad scores certain touchpoints obtain was due to their communication or due to lack of communication, or the way they used to communicate. The intent of this study is to have focused communication delivered at those touch points. Considering what was expected by the patient, and to address them in a proactive manner. This could improve the satisfaction scores in those specific touch points as well. Thus, this improvement would help the overall net promoter scores to be as targeted. This can be done by training the staff, and thus creating an awareness on their communication style, their behavior, and its impact on the customer satisfaction. Also, to make the employees understand the importance of the Net Promoter Scores. When the team understands that the customer is to be served well, and their communication matters in alleviating the anxiety and creating the first impression to every customer who walks in. To make it lasting, the first impression must be a good one. The communication across the care continuum matters especially at the front office. Mainly due to the first nonclinical contact happening at the front office. There are many literatures available abroad on customer satisfaction. Indigenously there is a dearth of resources addressing this specific problem. To address this problem this study is selected. "When you make things right, you increase trust, loyalty, and advocacy." - Shep Hyken .